KEMAMPUAN MENULIS TEKS PERSUASIF BERDASARKAN MEDIA IKLAN AUDIOVISUAL PADA SISWA KELAS VIII SMP NEGERI 1 ULUERE KABUPATEN BANTAENG - Sehati Nyambe; Usman Usman (TITIK DUA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2022)
Ability to Write Persuasive Texts Based on Audiovisual Advertising Media in Class VIII Students of SMP Negeri 1 UluereBantaeng Regency. This study aims at the ability to write persuasive texts based on audiovisual advertising media in terms of structure, application and characteristics of language use. This research belongs to the type of quantitative description research. The research instrument used was a written test. The results showed that: (1) the ability to write persuasive texts in terms of structure, namely students who scored 78-100 found 12 students with proportions (36.36%) while students who scored 0-74 revealed 21 students with proportions (63 ,64%) is included in the category of quite capable. (2) writing persuasive texts if it can be viewed in terms of linguistic rules, namely students who get a score of 78-100 get 18 students with a proportion (54.54%) while students who score 0-74 get 15 students with a proportion (45.46% ) is included in the capable category. (3) the ability to write persuasive texts when viewed in terms of the characteristics of language use, namely students who scored 78-100 had 15 students with a proportion (45.45%) while students who scored 0-74 obtained 18 students with a proportion (54.55 %) ) is included in the category of quite capable. This shows that the ability to write persuasive texts based on audiovisual advertising media in class VIII SMP Negeri 1 Uluere Bantaeng Regency is included in the quite capable category.